2013
DOI: 10.5120/13443-1343
|View full text |Cite
|
Sign up to set email alerts
|

Forecast Global Carbon Dioxide Emission using Swarm Intelligence

Abstract: The tremendous effects of air quality in large cities have been considered a severe environmental problem all over the world. Therefore, the international community agreed to develop air quality standards to monitor and control pollution rates around industrial communities. Harmful emission into the air is a sign that could extremely affect man's health, natural life and agriculture. Forecasting models is essential for predicting air quality. CO 2 emissions have been an international concern because of fossil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Different parametric models of ARIMA were constructed and different metrics were adopted to evaluate each ARIMA model. Reference [5] proposed a swarm intelligence methodology for the forecast of global CO 2 emission. Reference [6] employed bee algorithm and artificial neural network to forecast world CO 2 emission.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different parametric models of ARIMA were constructed and different metrics were adopted to evaluate each ARIMA model. Reference [5] proposed a swarm intelligence methodology for the forecast of global CO 2 emission. Reference [6] employed bee algorithm and artificial neural network to forecast world CO 2 emission.…”
Section: Introductionmentioning
confidence: 99%
“…Reference [11] predicted global CO 2 emission using two artificial neural network models namely neural network auto-regressive with exogenous input model and the evolutionary product unit neural network model (EPUNN). The authors in [11] adopted the same input and output variables as those reported in [5]. Reference [11] concluded that the evolutionary approach provided more stable result in the test data than the multilayer neural network.…”
Section: Introductionmentioning
confidence: 99%